The Effect of Audiolingual Method on Vocabulary Ability of the Fifth Grade Students of SDN 009 Tenggarong Seberang - Yunita Sinaga; Kartika Puspandari (Departement of Mathematics Education, 2023)
Audio-lingual method is one of the teaching methods in teaching vocabulary. The fact indicated that teaching vocabulary by using audio-lingual method gave better results than without using audio-lingual method at the fifth grade students of SDN 009 Tenggarong Seberang. The purpose of the study was intended to find out whether using audio-lingual method increase vocabulary ability of the fifth grade students of SDN 009 Tenggarong Seberang. In addition, the hypothesis of this study was: “Using audio- lingual method increases vocabulary ability of the fifth grade students of SDN 009 Tenggarong Seberang.” This study used experimental design. The population of the research was the fifth grade students of SDN 009 Tenggarong Seberang with the total number of the students was 47 students, and the sample taken was 30 students. The instrument of this study was a written test in the forms of multiple choices. The data of the study were scores on vocabulary. To analyze the data and to carry out the hypothesis testing, the researcher used t-test formula. It was proved by the value of t-computed which was greater than the value of t-table. From the result of computation by using t-test, it was found that the value of t-computed was 3.129, whereas the value of t-table at p=0.05 and degrees of freedom = Na + Nb – 2 = 28 was 2.048. As the result, the value of t-computed was greater than the value of t-table (3.129 > 2.048). Thus, the result of the research was read as “Using audio-lingual method significantly increases vocabulary ability of the fifth grade students of SDN 009 Tenggarong Seberang.”